Analisa Kestabilan Peralihan Multimesin Pada Sistem Tenaga Listrik Wilayah Riau - Reza Abdilla; Dian Yayan Sukma (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
Electrical energy is one of the energies that become a major part of human survival. Without electrical energy some human activities will be hampered such as trade, industry, education, etc. Within the area including Riau, the power system stability is very important. Power system stabilityare classified into three types, one of which is transient stability. This study aims to calculate and analyze the exact critical clearing time so that the system remains stable at the time of threephase symmetrical fault. The method used are fast decoupled method for power flow studies and the runge-kutta 4th order method to determine the rotor angle and critical clearing time using Matlab software. This study indicated that Riau's electric power system will remain stable if the critical clearing time is not more than 0.26 seconds.Keyword : Transient Stability, Three Phase Symmetrical Fault, Critical Clearing Time, Runge-kutta 4th Order Method